2015
DOI: 10.1002/nbm.3320
|View full text |Cite
|
Sign up to set email alerts
|

MRS: a noninvasive window into cardiac metabolism

Abstract: A well-functioning heart requires a constant supply of a balanced mixture of nutrients to be used for the production of adequate amounts of adenosine triphosphate, which is the main energy source for most cellular functions. Defects in cardiac energy metabolism are linked to several myocardial disorders. MRS can be used to study in vivo changes in cardiac metabolism noninvasively. MR techniques allow repeated measurements, so that disease progression and the response to treatment or to a lifestyle intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 255 publications
1
33
0
Order By: Relevance
“…Proton MR spectroscopy (MRS) has proven a valuable tool to study cardiac metabolism . It has been shown that myocardial triglyceride (TG) levels are dependent on age, diet, and circadian rhythm in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Proton MR spectroscopy (MRS) has proven a valuable tool to study cardiac metabolism . It has been shown that myocardial triglyceride (TG) levels are dependent on age, diet, and circadian rhythm in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“… 5 reported average water peak linewidths of 8.6 Hz (1.5 Hz) and 10.7 Hz (0.4 Hz) at 1.5 T, respectively; however, at this field strength, linewidths are expected to be approximately half the widths of those observed at 3 T. The narrow linewidth at 3 T in this study was achieved via: (1) a small voxel size; (2) the use of IVS for robust localisation to the interventricular septum; (3) a sophisticated image-based B 0 shimming strategy; and (4) a non-water suppressed MRS sequence in conjunction with ECG triggering and navigator respiratory-motion tracking, which allowed for prospective and retrospective motion correction, as well as frequency alignment and phase correction during post-processing. Moreover, the measurements shown here were acquired on a 3 T system, while most 1 H CMRS studies so far were performed at 1.5T 1 . The increased field strength results in a higher SNR and thus counteracts SNR loss resulting from the small voxel size.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance spectroscopy (CMRS) is becoming increasingly popular as a non-invasive probe of myocardial metabolism 1 , permitting healthy and pathological conditions to be studied using different endogenous nuclei. Of these, phosphorus ( 31 P) is the most widely investigated, reflecting the crucial role of phosphorus metabolites in myocardial energetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAGNETIC RESONANCE SPECTROSCOPY (MRS) has shown promising evidence as a noninvasive tool to gain valuable insights into cardiac metabolism of in vivo healthy and diseased hearts . Proton MRS ( 1 H‐MRS) allows quantifying myocardial triglyceride (TG) and creatine (CR) content .…”
mentioning
confidence: 99%